Enhancing Arabic Language Proficiency in Islamic Boarding Schools: A Comprehensive Study - Fakhiroh, Najiyah; Hikmah, Khizanatul (Indonesian Journal of Islamic Studies, 2023)
This qualitative research study investigates the planning, implementation, and evaluation of Arabic language learning at Ar-Rohmah Putri II Islamic Boarding School in Malang, Indonesia. The research aims to elucidate the intricacies of Arabic language development within the context of Islamic boarding schools, emphasizing its pivotal role. Data was gathered through observation, interviews, and documentation analysis, employing the interactive data analysis technique by Miles and Huberman. The findings reveal three key aspects: 1) meticulous planning of Arabic language curriculum, learning tools, and language competency enhancement programs; 2) effective implementation aligned with educational objectives and the integral curriculum based on tauhid (Islamic monotheism); 3) multifaceted evaluation methods encompassing both student assessments and teacher performance evaluations. This research contributes to a deeper understanding of Arabic language education in Islamic boarding schools and its implications for educational practices worldwide. Highlights: Curriculum Planning: A crucial step in Arabic language learning within Islamic boarding schools involves meticulous curriculum planning. Effective Implementation: The successful execution of language programs aligns with educational objectives and the integral curriculum. Comprehensive Evaluation: A multifaceted evaluation approach assesses both students' Arabic language proficiency and teachers' performance. Keywords: Arabic language learning, Islamic boarding schools, Curriculum planning, Implementation evaluation, Language competency.